Measuring What Matters: Monitoring The Contribution Of A New Mining Project To Community Sustainability (Society for Mining, Metallurgy & Exploration, 2007)
Ravensthorpe Nickel Operation (RNO) is a major new mine and processing plant currently being constructed by BHP Billiton in a ?green field? site near the small town of Ravensthorpe, about 150 km west of Esperance and six hours drive from Perth in Western Australia. Ensuring that the project has a positive overall impact on the surrounding region and that this extends well beyond the life of the operation will be a major challenge for RNO, state and local government, and the local community. For the last two years, the Centre for Social Responsibility in Mining (CSRM) has been assisting RNO management and the RNO Community Liaison Committee to develop a community sustainability monitoring framework for the project. This paper reports on the process that was used to develop the framework, describes the main elements and briefly discusses key learnings from the exercise.